Isolated Left Coronary Ostial Stenosis: A Case Report - Hong, Mee Jae (Korean J Intern Med, 1990)
A patient with isolated left coronary ostial stenosis proved by coronary angiography is presented. Isolated left coronary ostial stenosis is a rare condition of unknown etiology. Unique clinical and angiographic profiles are discussed in detail with a review of the literature, along with a suggestion of a natural history distinct from that usually seen in atherosclerotic coronary diseases.